2014
DOI: 10.3748/wjg.v20.i22.6924
|View full text |Cite
|
Sign up to set email alerts
|

Non-surgical treatment of post-surgical bile duct injury: Clinical implications and outcomes

Abstract: Endoscopic or percutaneous hepatic approaches can be used as an initial treatment in type 1 and 2 BDIs. However, surgical intervention is a treatment of choice in type 3 BDI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 25 publications
0
28
0
2
Order By: Relevance
“…Catheter stenting is the first-line treatment, and subsequent diversion of the fistula by endoscopic or percutaneous transhepatic techniques is necessary in addition to drainage of the biloma cavity [1][2][3][4][5][6]. Intrahepatic diversion of the biliary system decreases the intrabiliary pressure by rerouting the flow of bile away from the defect in the bile duct.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Catheter stenting is the first-line treatment, and subsequent diversion of the fistula by endoscopic or percutaneous transhepatic techniques is necessary in addition to drainage of the biloma cavity [1][2][3][4][5][6]. Intrahepatic diversion of the biliary system decreases the intrabiliary pressure by rerouting the flow of bile away from the defect in the bile duct.…”
Section: Discussionmentioning
confidence: 99%
“…Sandha et al [5] reported that temporary biliary stenting for 4 to 6 weeks yielded satisfactory results in more than 90% of 207 consecutive patients with severe bile leaks or strictures. However, bile duct injuries, especially bile leaks concomitant with biliary strictures, that cannot be definitively treated with percutaneous or endoscopic techniques require surgical repair [3][4][5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For BDI detected soon after surgery, such as injury without local inflammation can be performed with primary repair (38). In cases with abdominal infection, biliary peritonitis, vascular injury, or other complicated conditions, delayed repair should be performed after the measures of controlling bile leakage and infection and improving the patient's general condition (39,40). Although the early idea holds that the timing of delayed repair should be at least 3 months away from the injury, current evidence suggests that definitive repair surgery may be performed 4-6 weeks after local inflammation and infection are effectively controlled (41,42).…”
Section: Appropriate Timing For Repairmentioning
confidence: 99%